Electronic Tongue Technology Applied to the Analysis of Grapes and Wines: A Comprehensive Review from Its Origins - Celia Garcia-Hernandez; Cristina Garcia-Cabezon; Maria Luz Rodriguez-Mendez; Fernando Martin-Pedrosa (Chemosensors)
The electronic tongue (ET) and bioelectronic tongue (bioET) technologies have emerged as innovative and promising tools for the characterization and quality control of complex liquid matrices such as grape musts and wines. These multisensor systems, based on electrochemical detection and chemometric analysis, provide global and rapid information about taste-related attributes, antioxidant content, and other critical parameters, offering an alternative or complement to traditional analytical methods. This review explores the principles, development, and applications of ET and bioET in the wine industry, highlighting their capacity to assess grape ripeness, monitor fermentation, determine wine aging, detect adulterations, and support geographical and varietal authentication. Special attention is paid to advances in sensing materials—such as conducting polymers, metal nanoparticles, and enzymes—and the construction techniques of sensors and biosensors, which have improved ET performance. Finally, the potential of these technologies as cost-effective, portable, and on-site tools aligns with the demands of Industry 4.0 and next-generation smart agriculture and food production systems.